Idiopathic Pulmonary Fibrosis Registry China study (PORTRAY): protocol for a prospective, multicentre registry study. Issue 11 (11th November 2020) - Xie, Bingbing; Ren, Yanhong; Geng, Jing; He, Xuan; Ban, Chengjun; Wang, Shiyao; Jiang, Dingyuan; Luo, Sa; Chen, Qihang; Liu, Min; Feng, Ruie; Zhao, Ling; et al.
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive and lethal lung disease characterised by a fibrotic histological pattern found in usual interstitial pneumonia. Its causes, pathogenesis, clinical phenotype and molecular mechanisms are poorly defined. Large-scale, multicentre studies are warranted to better understand IPF as a disease in China, its associated risk factors, clinical characteristics, diagnosis, disease progression and treatment. Methods and analysis: The Idiopathic Pulmonary Fibrosis Registry China Study (PORTRAY) is a prospective, multicentre registry study of patients with IPF in China. Eight hundred patients will be enrolled over a 36-month period and followed for at least 3 years to generate a comprehensive database on baseline characteristics and various follow-up parameters including patient-reported outcomes. Biological specimens will also be collected from patients to develop a library of blood, bronchoalveolar lavage fluid and lung biopsy samples, to support future research. As of 15 December 2019, 204 patients from 19 large medical centres with relatively high IPF diagnosis and treatment rates had been enrolled. Patient characteristics will be presented using descriptive statistics. The Kaplan-Meier method will be used for survival analyses. Repeated measures will be used to compare longitudinal changes in lung function, imaging and laboratory tests. Results following analysis have been projected to be available by July 2025. Ethics and dissemination: The study protocol was reviewed and approved by the Institutional Review Board from all the study sites currently recruiting patients. Study results will be published in peer-reviewed journals. Trial registration number: NCT03666234 .